Economics of eBay's buyer protection plan - J. Christopher Westland (Financial Innovation, 2015)
Background: This paper explores the financial viability of eBay's Buyer Protection Plan. Methods: We explore their warranty model assuming exponential auction listing and claims times, under competing assumptions of Normal (classical portfolio theory) versus Paretian claims (industry practice) distributions using a normative algorithm. EBay's model viability was analyzed under three risk metrics - mean-variance risk of classic portfolio theory; value at risk used in regulation such as the Basel Accords; and tail value at risk which is preferred by academics. Results: Five main findings of the research are: (1) long-term financial viability is set by boundary conditions that can be managed in eBay's contract terms, (2) commonly used but simplistic assumptions of Gaussian distributions of contract failures can be misleading, and keeping the Buyer Protection Plan viable demands more realistic distributions, (3) value at risk measures provide more information about viability than expectations, (4) tail value at risk measures an lead to sudden and extreme variations in fund value over the parameter range and flawed contracting decisions, and (5) tail value at risk is the preferable risk measure for assessing Buyer Protection Plan viability, but it needs to be used with an assumption of Lomax contract failures to support profitable contracting. Conclusions: Our analysis showed substantial improvements in claims management when tail value at risk measures were used instead of conventional VaR measures. This implies that current strategies, and prices for coverage may result in losses to eBay, in current practice.
Keywords: 650; Auctions; Insurance; Risk; E-markets; Trust; Reputation